2010
DOI: 10.1128/jvi.01748-09
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Induces the Interferon Response via the DNA Sensor ZBP1

Abstract: Human cytomegalovirus (HCMV) is a member of the betaherpesvirus family that, unlike other herpesviruses, triggers a strong innate immune response in infected cells that includes transcription of the beta interferon gene via activation of interferon regulatory factor 3 (IRF3). IRF3 activation requires signaling from pattern recognition receptors that is initiated by their interaction with specific pathogen-associated molecules. However, while IRF3-activating pathways are increasingly well characterized, the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
184
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(192 citation statements)
references
References 86 publications
(148 reference statements)
5
184
2
1
Order By: Relevance
“…The innate immune response to HCMV involves an orchestrated system composed of multiple receptors residing in different cellular compartments (1,4,7,29). Characterizing of these receptors and understanding their function and networking, as well as strategies used by HCMV to counteract their activities, are of paramount importance for HCMV control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The innate immune response to HCMV involves an orchestrated system composed of multiple receptors residing in different cellular compartments (1,4,7,29). Characterizing of these receptors and understanding their function and networking, as well as strategies used by HCMV to counteract their activities, are of paramount importance for HCMV control.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the promyeolcytic leukemia protein, a regulator of type I IFN response, is counteracted by HCMV-encoded immediate early 1 protein (IE1) (6). A cytoplasmic dsDNA sensor, ZBP1, activates IRF3 on infection, and its overexpression inhibits HCMV replication (7). IFN-inducible protein IFI16 modestly inhibits HCMV by blocking Sp1-mediated transcription of HCMV-encoded UL54 and UL44, which are involved in viral DNA synthesis (8).…”
Section: Ripk2mentioning
confidence: 99%
“…DAI is required for HSV-1-induced IFN production in mouse microglial cells, astrocytes, and fibroblast line L929 (10,45). Human foreskin fibroblasts also require DAI for IFN production in response to CMV infection (46). In contrast, DAI is dispensable for the DNA-triggered IFN production in mouse embryo fibroblasts and dendritic cells (44).…”
Section: Discussionmentioning
confidence: 99%
“…DAI has now been show to be important for the antiviral immune response to Human cytomegalovirus (HCMV). It was observed that DAI was essential for IRF3 activation and IFNβ expression triggered by HCMV, and that overexpression of DAI could inhibit replication of HCMV [36]. From this work, the authors suggested that DAI is the principal PRR for the IFNβ response to HCMV infection.…”
Section: Cytosolic Sensing Of Viral Dna For Ifnβ Inductionmentioning
confidence: 85%
“…Although novel downstream signalling components involved in DNA sensing pathways, such as DDX3 [34][35][36] and STING [37], continue to be identified, and although high mobility group proteins have recently been implicated in delivering nucleic acid to PRRs for detection [38], identification of cytoplasmic DNA PRRs (that could bind DNA and transmit a signal to TBK1) remains elusive.…”
Section: Cytosolic Sensing Of Viral Dna For Ifnβ Inductionmentioning
confidence: 99%